The common and the unfolding in the solidarity economy from ecological sanitation - Machado, Gustavo Carvalhaes Xavier Martins Pontual; Maciel, Tania Maria de Freitas Barros; Thiollent, Michel Jean Marie (Saúde e Sociedade, 2021)
As sanitation conditions in Brazil are precarious in rural areas, it is important to build territorial actions that value culture and strengthen good living based on solidarity economy to achieve sustainable solutions. Dardot and Laval see the “common” as a counterpoint to the current political and economic context, in which individuals assume the role of protagonists in their lives and manage the “commonalities” for their community. In this approach, the Oswaldo Cruz Foundation (Fiocruz), through the Observatory of Sustainable and Healthy Territories of Bocaina (OTSS), constituted an ecological sanitation research in the Caiçara Community of Praia do Sono, in Paraty, with the participation of the community during thewhole process and, through a qualitative evaluation, the relationship between the community and the common could be understood. Local builders were hired as social mobilizers, thus valuing endogenous resources. Through this articulation, joint action with public agencies was sought to foster actions that came from the community itself and inclusive public policies that put a society at the center of the process. Supported by the concept of common and by semi-structured interviews, this psychosocial study examines the unfolding of the solidarity economy.